Between the mountain and the sky : a mother's story of love, loss, healing, and hope - Doyne, Maggie; Miller, Shannon Lee (Harper Horizon, 2022)
"Maggie's story begins in suburban New Jersey, in a comfortable middle-class family that supports her decision to travel the world during a gap year before starting college. During her travels, the trajectory of her life alters when she has a surprise encounter with a Nepali girl breaking rocks in a quarry. Maggie decides to invest her life savings of five thousand dollars to buy a piece of land and open a children's home in Nepal. That home becomes Kopila Valley Children's Home, and eventually, the nonprofit Maggie launches, the BlinkNow Foundation, also starts the Kopila Valley School, which provides tuition-free education for more than four hundred students. Maggie and BlinkNow's work have been recognized around the world for their innovative, sustainable work. However, this book isn't a how-to for fledging philanthropists or nonprofit founders--it's a coming-of-age story about a young woman suspended between two worlds, as well as the love, loss, healing, and hope she experiences along the way"--